Landelijk kunstenaars protest in de Jaap Edenhal. Persiflage op minister van Doorn. Serie van 3 foto's - Dijk, David van,
Landelijk kunstenaars protest in de Jaap Edenhal. Persiflage op minister van Doorn. Serie van 3 foto's.